Integrating Historical Methodology For The Objective Reconstruction Of Islamic Education Narratives Based On Authoritative Sources - Asti Triasih; Ani Maghfiroh; Zuhdiyah; Maryamah; Nyayu Soraya (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study examines the integration of educational historical methodology in reconstructing Islamic education narratives in a more objective and contextually grounded manner. While Islamic educational historiography has often been shaped by normative and descriptive approaches, this research argues that a systematic historical-critical framework is necessary to ensure analytical rigor and epistemological transparency. Employing qualitative library research, the study applies classical stages of historical inquiry heuristics, source criticism, interpretation, and historiographical synthesis combined with hermeneutical and discourse-oriented analysis. The findings reveal that Islamic education constitutes a dynamic historical construction shaped by the interaction of text, authority, institutions, and socio-political transformation. Core elements such as ‘ilm, ulama authority, transmission networks, and the institutionalization of madrasah and pesantren developed through processes of negotiation and adaptation rather than linear progression. By critically verifying sources and situating concepts within their historical horizons, the integrated methodology minimizes ideological bias and avoids normative reductionism. The originality of this study lies in its systematic synthesis of historical criticism, hermeneutics, and discourse analysis into a unified methodological framework for Islamic educational historiography. The research contributes theoretically by strengthening methodological discourse in Islamic education studies and practically by providing a reflective foundation for context-sensitive educational reform in contemporary Muslim societies.